Estabilización escapular vs técnicas de movilización de hombro en pacientes mujeres de 45 a 65 años sobre la movilidad en abducción de hombro, en capsulitis adhesiva del Hospital General Andino. Periodo septiembre diciembre 2024 - Chimbo Patin, Jessica Nataly (2025)
Research background: adhesive capsulitis is mainly characterized by limitation of shoulder abduction, pain, muscle weakness and joint stiffness, being a very common problem in women from 45 to 65 years old, which makes it impossible to perform daily life activities, recreational activities and household chores. Research objective: to compare the shoulder mobilization technique versus scapular stabilization on active mobility in shoulder abduction in women with adhesive capsulitis. Research methodology: it is a quantitative research with an experimental design with intervention, the population was 28 female patients from 45 to 65 years old, a shoulder mobilization and scapular stabilization protocol was designed, it was applied three sessions per week with a total of 12 interventions. Results obtained: after the intervention showed an increase in shoulder abduction ROM, specifically the scapular stabilization exercises that were applied to group B, achieved 92.9% of significant improvement in shoulder abduction in patients who presented adhesive capsulitis, followed by 78.6% achieved complete shoulder abduction mobility, which represents group A that applied the shoulder mobilization technique. Conclusion: stabilization exercises had favorable results in the recovery of the articular range of active shoulder abduction which indicated their effectiveness in female patients with adhesive capsulitis, on the other hand, the shoulder mobilization technique presented significant results in the reduction of pain in adhesive capsulitis.